Strategi Penguatan Children’s Well-Being melalui Media Loose Parts dalam Implementasi Kurikulum Merdeka di PAUD - Eka Gusriani; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Children’s well-being is a crucial foundation in the implementation of the Merdeka Curriculum in early childhood education (ECE), yet field facts indicate that academic pressure still hinders children’s emotional growth. This study aims to analyze strategies for strengthening children’s well-being throught the use of loose parts media and a play-responsive teaching approach. Using a descriptive qualitative method with a library research technique, primary data were sourced from PAUD to SD transition policy documents and international pedagogical protocols, while secondary data were obtained throught the synthesis of reputable literature. The result show that the intentional use of loose parts media can significantly enhance children’s agency and emotional resilience by removing learning product pressure. Furthermore, repositioning the teacher’s role as a play partner is proven to create a more humanistic and inclusive learning ecosystem. These findings recommend the integration of well-being as a core foundation in every play activity planning to ensure children’s fundamental right to happiness in learning